Investigation on Effects of Untreated and Cryogenically Treated Brass Wire on M42 Hss In WEDM Process - Singh, Ranjit (My University, 2016)
M42 High speed steel is a finest cobalt based high speed steel having high hot hardness and better hot hardness. These properties makes this steel an outstanding option for machining high-strength and pre-hardened steels, high-hardened alloys, and the difficult-to-machine, nonferrous super alloys used in the aerospace, oil, and power generation industries. Its applications are twist drills, milling cutters, taps, reamers, broaches, saws, knives, and thread rolling dies. The inherent problem of machining these high speed steels with conventional machining processes necessitate the use of alternative machining processes. The wire electrical discharge machining(WEDM) processes has been found to be a good alternative of conventional machining processes. Less work has been reported for predicting the performance of WEDM processes particularly for the M42 HSS. In the present work, the effect of shallow cryogenated brass wire on the M42 HSS is compared with the results of untreated wire on M42. The empirical modeling of process parameters of the WEDM has been carried out for the M42 HSS using a well known experimental design approach called Response Surface Methodology(RSM). The parameters such as pulse-on, pulse-off, spark gap voltage and wire feed have been selected as input variables keeping current and wire tension constant. The performance has been measured in terms of cutting speed(CS), surface roughness(Ra) and dimensional deviation(DD).
Keywords: transfer, microstructure, intensity